Stability Analysis of Block Logical Dynamical Systems and Its Application in Logical Networks With Time Delay - Li, Haitao; Li, Yalu; Li, Wenrong; Liu, Yansheng (IEEE transactions on automatic control, 2024)
A new class of nonlinear systems, block logical dynamical systems (BLDSs), is introduced in this note. The existence and uniqueness of solution to BLDSs are first investigated. Then, the topological structure and global stability of BLDSs are analyzed, and a novel criterion is presented to verify the global stability of BLDSs. Finally, the stability of BLDSs is used to study the stability of logical networks subject to time delay. It is shown that the introduction of BLDSs can considerably reduce the computational complexity of verifying the stability of logical networks with time delay.